Buletin FKA Edisi 2023 / Dr. Kuan Woei Keong - Kuan, Woei Keong (Unit Penerbitan PKAPP, 2024)
Pasukan Editorial: Prof. Madya Ts. Dr. Kay Dora Abd Ghani Prof. Madya Dr. Noorsuhada Md Nor Prof. Madya Ir. Dr. Ng Kok Shien Prof. Madya Dr. Tey Li Sian Dr. Salina Alias Ir. Dr. Goh Lyn Dee Ts. Dr. Mohd Ikmal Fazlan bin Rosli@Rozli Ahmad Syauqi Md Hasan Juliana Idrus